Audit Quality: The Impact of Expertise, Independence and Ethics of Professional Accountant A Crosssectional Study - Adam Ramdani (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2021)
This study aims to determine the effect of expertise, independence, and ethics on audit quality at the Inspectorate of West Java Province. The study in the initial review of this study found that the audit quality is shown in the opinion given by the examiner, including the opinion "Reasonable Without Exception" is a professional audit statement regarding the "fairness" of the financial statements, not a "guarantee" that no fraud was encountered or the possibility of the occurrence of fraud. Fraud in the future also on the problem of procurement of goods and services that cause indications of regional losses, management of accounts that are not following the provisions, causing potential fraud, management of fixed assets that are still problematic both in terms of administration and utilization and the problem is that the value is still found to be immaterial so that the Audit Board of the Republic of Indonesia gives an opinion "Reasonable Without Exception" (RWE). In the first stage of this research, namely, test the validity and reliability of all valid and reliable variables. In the second stage of conducting a correlation analysis for Expertise, Independence and Ethics on Audit Quality, showing a significant correlation, the relationship between Expertise and Audit Quality obtained a result of 0.813. Independent Relationship with Audit Quality obtained results of 0.751, and the result of Ethics Relationship with Audit Quality obtained results of 0.812. In the third stage, partial regression analysis for all variables proved to be significant, and it was found that the regression coefficient value of Expertise on Audit Quality obtained the result of 0.411. The independent regression coefficient value on Audit Quality is 0.235, and the Ethics regression coefficient on Audit Quality is 0.403. Likewise, in the fourth stage, simultaneous multiple regression analysis of expertise, independence, and ethics has a significant effect on Audit Quality with a total effect of 83.7%.